Recycling of carbonaceous iron-bearing dusts from iron & steel plants by composite agglomeration process (CAP). (9th August 2017) - Zhang, Y.B.; Liu, B.B.; Xiong, L.; Li, G.H.; Jiang, T.
Abstract : A composite agglomeration process (CAP) is carried out to recycle the carbonaceous iron-bearing dusts generated from the Iron & Steel companies in order to reduce the environmental pollution caused by the hazardous dusts and make good use of the valuable elements contained in the dusts. In current study, all the dusts are first made into green pellets and used as one part of agglomeration feeds. Effects of the properties of the pelletised feeds on the agglomeration indexes of CAP and the mineralisation, metallurgical characterisation of the CAP products were investigated. It is found that the dust dosage is increased from 7 wt.% by traditional sintering process to 20 wt.% by CAP. Coke breeze consumption is reduced by 21.25 kgcoke /tproduct in the CAP with 20 wt.% pelletised feed proportion, indicating the carbon component in the dusts is effectively utilised. The mineralisation characterisations of CAP products are clarified by using optical microstructure and SEM-EDS analyses. Results also demonstrate that metallurgical performances of the CAP products are good and the CAP products are qualified for blast furnace burdens.